INSTITUTIONAL ANALYSIS OF FOOD SECURITY IN SABAH - Firdausi Suffian; Ika Suzieana Jamluddin; Faridah Suffian (Journal of Islamic, Social, Economics and Development, 2022)
The key concern over food security boils down to the role of institutions to prioritizethe agenda in agriculture policy. The role of institutions plays primary role to orchestrate foodpolicy agenda, coordinate and implement agro-food policy so that food sector can contributeat least sufficient supply with less dependent on food import. The pandemic-induced crisis hasmanifested the importance of food security across the globe. Lockdown and trade restrictionhave disrupted the food production supply chain and raised the concern over accessibility offood supply. The threats of food security are policymaker paying less attention on theimportance of food sector rather focus on the lucrative industrial crops sectors. Worst still,industrial crops sector only focusses on extractive activities and limited downstream to supportthe local agro-food and sub-sectors. This research explores food security issues in Sabah whichis one of the rich resource states in Malaysia. Agriculture sector contributes significantly to thestate economy and mostly dominated by industrial crops. The over dominance of industrialcrops activities made the state dependent on food import which constituted the largest importof the state. Though industrial crops are one of the important export gains for the state butdepending on food import may lead to higher food prices, which will push governments toimpose price ceilings, further stressing supply capacity. This will hurt the population and mostvulnerable ones. So, this research intended to understand food security issues and constrainingfactors for expanding agro-food production